Simultaneous Videofluoroscopy and Endoscopy for Dysphagia Evaluation in Preterm Infants—A Pilot Study - Kamity, Ranjith; Ferrara, Louisa; Dumpa, Vikramaditya; Reynolds, Jenny; Islam, Shahidul; Hanna, Nazeeh (Frontiers in Pediatrics, 2020)
Introduction: The assessment of dysphagia in preterm infants has been limited to clinical bedside evaluation followed by videofluoroscopic swallow study (VFSS) in selected patients. Recently, fiberoptic endoscopic evaluation of swallowing (FEES) is being described more in literature for preterm infants. However, it is unclear if one test has a better diagnostic utility than the other in this population. Furthermore, it is also unclear if performing FEES and VFSS simultaneously will increase the sensitivity and specificity of detecting dysphagia compared to either test performed independently. Objectives: The primary objective of this study is to evaluate the feasibility of performing VFSS and FEES simultaneously in preterm infants. Our secondary objective is to determine whether simultaneously performed VFSS-FEES improves the diagnostic ability in detecting dysphagia in preterm infants compared to either test done separately. Methods: In this pilot study, we describe the process involved in performing simultaneous VFSS-FEES in five preterm infants (postmenstrual age ≥36 weeks) with dysphagia. A total of 26 linked VFSS-FEES swallows were analyzed, where the same bolus during the same swallow was compared using simultaneous fluoroscopy and endoscopy. The sensitivity and specificity of detecting penetration and aspiration were evaluated in simultaneous VFSS-FEES compared with each test done independently. Results: Our results demonstrated that performing simultaneous VFSS-FEES is feasible in preterm infants with dysphagia. All patients tolerated the procedures well without any complications. Our pilot study in these five symptomatic preterm infants demonstrated a low incidence of aspiration but a high incidence of penetration. Simultaneous VFSS-FEES (26 linked swallows) improved the ability to detect penetration compared to each test done separately. Conclusion: To our knowledge, this study is the first to demonstrate the feasibility of performing VFSS and FEES simultaneously in symptomatic preterm infants with dysphagia resulting in potentially higher diagnostic yield than either procedure done separately.